Prosthetic Aortic Valve Stenosis in End-Stage Renal Failure - Michael Mao; Mirelle El Ters; Sunil Mankad; Mira Keddis; Soon Park; Qi Qian (International Journal of Nephrology)
Although renal failure is one of the known comorbidities associated with rapid progression of aortic stenosis, it is unclear whether hemodialysis alters the progression of prosthetic aortic valve stenosis. We describe a 79-year-old female who underwent bioprosthetic aortic valve replacement 8 years ago with stable prosthetic valve area for the initial 6 years. In the last two years, coinciding with the initiation of maintenance hemodialysis, she developed progressive prosthetic valve stenosis to the point of clinical decompensation. She underwent a second prosthetic aortic valve replacement with symptom resolution. This case suggests that circulating milieu in end-stage renal failure and dialysis can accelerate the progression of prosthetic aortic valve stenosis. More frequent clinical followup and surveillance echocardiogram for dialysis patients with bioprosthetic aortic valve may facilitate timely management of valvular stenosis.